Prevalence and sociodemographic correlates of DSM-5 eating disorders in the Australian population - Hay, Phillipa (J Eat Disord, 2015)
BACKGROUND: New DSM-5 diagnostic criteria for eating disorders were published in 2013. Adolescent cohort studies in the Australian community indicate that the point prevalence of DSM-5 eating disorders may be as high as 15% in females and 3% in males. The goal of the current study was to determine the 3-month prevalence of DSM-5 disorders in a representative sample of Australian older adolescents and adults. A secondary aim was to explore the demographic correlates of these disorders, specifically, age, gender, income, and educational attainment and presence of obesity. METHODS: We conducted and merged sequential cross-sectional population survey data of adults (aged over 15 years) collected in 2008 and in 2009 (n = 6041). Demographic information and the occurrence of regular (at least weekly over the past 3 months) objective and subjective binge eating, extreme dietary restriction, purging behaviors, and overvaluation of weight and/or shape, were assessed. RESULTS: The 3-month prevalence of anorexia nervosa and bulimia nervosa were both under 1% whereas the prevalence of binge eating disorder (BED) and sub-threshold BED were 5.6-6.9%. The prevalence of BED including overvaluation of weight/shape was 3%. Other specified and unspecified eating disorders including purging disorder were less common, under 1% to 1.4%. While people with eating disorders were generally younger than others, the mean age was in the fourth decade for anorexia nervosa and bulimia nervosa and in the fourth or fifth decade for all other disorders. Most people with eating disorders had similar household incomes and educational attainments to the general population. People with bulimia nervosa, BED and sub-threshold bulimia nervosa were more likely to be obese than people without an eating disorder. CONCLUSIONS: The findings support the expanded demographic distribution of eating disorders. There is a relatively high prevalence of BED compared to anorexia nervosa and bulimia nervosa. As it is in BED, obesity is a very common co-morbidity in bulimia nervosa.